2022
DOI: 10.1155/2022/6556867
|View full text |Cite
|
Sign up to set email alerts
|

Value of Combining Optical Coherence Tomography with Fundus Photography in Screening Retinopathy in Patients with High Myopia

Abstract: Objective. To explore the value of combining optical coherence tomography (OCT) with fundus photography in screening retinopathy in patients with high myopia. Methods. By means of retrospective study, 40 high myopia patients with retinopathy treated in our hospital from January 2020 to January 2021 were selected as the study group, and 40 healthy individuals in the same period were included in the control group. All patients received traditional ophthalmic examination, and accepted fundus fluorescence imaging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This was also in line with what Hao et al, who examined a group consisting of 40 myopia patients with retinopathy and 40 healthy individuals who were part of the control group during the same time period. The authors' findings showed that the study group's nerve thickness was significantly different from that of the control group in terms of both the nerve thickness above and below the optic disc as well as the temporal and nasal nerve thickness of the optic disc (P < 0.001) [23].…”
Section: Discussionmentioning
confidence: 86%
“…This was also in line with what Hao et al, who examined a group consisting of 40 myopia patients with retinopathy and 40 healthy individuals who were part of the control group during the same time period. The authors' findings showed that the study group's nerve thickness was significantly different from that of the control group in terms of both the nerve thickness above and below the optic disc as well as the temporal and nasal nerve thickness of the optic disc (P < 0.001) [23].…”
Section: Discussionmentioning
confidence: 86%
“…It noted that OCT will be added to FP screening for chorioretinal disorders in the future. The studies published to date focus on specific pathologies, such as Jain, N.'s quantitative comparison of drusen segmented on SD-OCT versus drusen delineated on color fundus photographs [38], or Hao Y's paper [39], which indicated that the combination of OCT with fundus photography can effectively identify disease. In a study of high levels of myopia, the sensitivity, specificity, PPV, and NPV of OCT combined with fundus photography were more than 94.0%, which were significantly higher than OCT or fundus photography alone (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%